Influência das características fenotípicas de machos de Heteragrion consors (Odonata: Megapodagrionidae) sobre sua permanência em áreas de encontro entre os sexos - Loiola, Geovanni Ribeiro (2008)
Heteragrion Consors Selys (Odonata: Megapodagrionidae) is a species of dragonfly inhabits streams in dense forests. Males remain resting perches on the banks of streams, while females acquire partner and visit places of oviposition. The daily variation of the abundance of males and ambient temperature, the time budget of males, the reproductive behavior and mating system of the species, the spatial distribution of males and assumptions that behavior (perching inert, perching flexing the abdomen, transition flight, foraging flight and agonistic flight) and body size of males affect retention and mobility in preferred roosts and determine distinct territorial strategies were investigated. To achieve these goals, including hypothesis tests, a population of H. Consors was monitored for 40 days in Duas Bocas Biological Reserve, Espírito Santo, southeastern region of Brazil, registering the behavior of 152 individuals, location in the environment and taking body measurements of 63 individuals. The species has a limited thermal tolerance to high incidence of solar radiation and uses shaded perches in the hottest times of the day, avoiding excessive body heat. Analyzing the 35 hours of sampling behavioral male inert and remain resting most of the time ( x =98.17%, SD= ± 7.58%), using the same perch for several consecutive days ( x =4.06 days; SD= ± 4.08; range=1-20 days), rarely performing transition flights ( x =0.16%, SD= ± 0.85%), foraging flights ( x =0.58%, SD= ± 1,06%) and agonistic flights ( x =0.34%, SD= ± 2.48%), or mating (0.4 matings/day). The male remains in contact with the female pre-copulatory tandem ( x =4.55 minutes, SD= ± 5.13, n=27.3 minutes), copulation ( x =15.98 minutes, SD= ± 7.13, n=79.9 minutes) and contact post-copulatory guarding ( x =10.07 minutes, SD= ± 7.8, n=40.3 minutes) of long duration, avoiding the loss of reproductive success and sperm competition with rivals. Behavioral characteristics investigated and body size had no influence on the ability to monopolization of specific points in the environment, although males with smaller body size perches attend higher (r=-0.3, P=0.01, n=135). It was not possible to separate different spatial strategies based on behavioral characteristics investigated and body size of males, but air conflicts and stay on the same perch for several days can mean territoriality. Sexual selection (intrasexual and intersexual) apparently operates at low intensity in the species, which has a low degree of sexual dimorphism. The mating system is not based on the monopolization of resources by males, consisting of an encounter-limited mating system, with rare encounters between males and females and abundant availability of oviposition sites. The impact on the longevity of male reproductive success deserves further investigation, because it tends to be characteristic influential in acquiring partner, with greater advantage for males to live longer and explore more reproductive events extremely rare. The abundance of females, fat and body symmetry in males, characteristics of the substrate submerged in segments with perches and speed of the water current are also variables that can determine the permanence of males in the same perch and visitation of females, also deserves further research